Small scale water resource management in Lok Dangkaan, Pitas: recharge and recovery strategies for water supply in coastal and rural communities - Fera Cleophas; Mohamad Zul Hilmey Makmud; Nur Zaida Zahari; Hardianshah Saleh; Assis Kamu; Mohd Khalizan Sabullah; Farrah Anis Fazliatul Adnan; Kawi Bidin (Faculty of Science & Natural Resources, UMS, 2024)
The recharge and recovery processes of water reservoirs in Lok Dangkaan, Pitas, aim to support sustainable water resource management for the local community. Situated in a coastal and rural area, the region faces unique challenges regarding water availability and quality.Currently, a small-scale water treatment plant incorporating Internet of Things (IoT) systems has been established to serve 40 households, providing an essential water supply. The water treatment plant system includes a water collection pond that plays a crucial role in maintaining a steady supply of water for the community. This pond depends on recharge from subsurface water to replenishes the pond. However, the most crucial aspect remains the water source, emphasizing the need for effective recharge and recovery strategies. Therefore, effective recharge and recovery strategies are essential, given the area's dependence on this water source to ensure a continuous and reliable water source, critical for the plant's operation and the community's needs. The research investigates both natural and artificial recharge methods to enhance the water collections pond replenishment and evaluates recovery practices to ensure efficient water extraction. Natural recharge processes, including precipitation infiltration and surface water seepage, are examined alongside artificial methods such as tube well and recharge basins. The study also explores the potential of stormwater capture as a supplementary recharge strategy. This is particularly vital in coastal and rural areas where surface water sources may be limited or unreliable, highlighting the importance of sustainable water resources management practices.